Analisis Regresi Linier Kelembaban Tanah dan Produksi Energi pada Plant-MFC Berbasis Padi untuk Pertanian Mandiri Energi - Kaila Zalfa Ashofa; Afifah Nurin Aisyah; Aulianisa Hanan Az Zuhri; Videnina Mizzani; Mariza Ainun Jariyah (SMA Trensains Muhammadiyah Sragen, 2026)
The global energy crisis and demand for environmentally friendly energy have driven the development of alternative bioelectrochemical technologies, such as the microbial fuel cell (MFC). This study analyses the effect of soil moisture on the electrical power generated by the MFC system. The research was conducted at Trensains Muhammal High School in Sragen from September to October 2025, using simple linear regression analysis. The analysis shows a regression equation of Y = 1.83 + 0.82X with a coefficient of determination (R²) of 0.994, indicating that 99.4% of the electrical power variability is explained by changes in soil moisture. The regression model was declared valid based on the F test (Fcount = 1258.7; p < 0.05), t test (tcount = 35.48; p < 0.05), and classical assumption tests (p > 0.05). The MFC system can produce 38.2 mW on an area of 100 cm², which is sufficient to power low-power devices. This technology has significant potential for use in sustainable agriculture and achieving SDGs 7 and 13.